PENGGUNAAN MESIN CRM DAN APLIKASI E - CHANNEL TERHADAP KEPUASAN NASABAH DI BANK BNI BATU AJI BATAM - SERLY HEKI RAHMAWATI; RAYMOND . (JURNAL ILMIAH KOHESI, 2020)
Advancements in technology make it easier for all activities of each individual in everything. One of the machines thatprovides convenience in conducting transactions is CRM engine. And one business application that provides bankingservices is E-Channel. Information technology applications in e-channels at Bank BNI consist of e-banking, short messagebanking, phone banking, e-channel applications are made to increase efficiency, and productivity while increasing revenuewith far better sales. The purpose of this study is to measure the partial and simultaneous influence of application CRMengine and e-channels on customer satisfaction at Bank BNI Batu Aji Batam. The research design used in this study iscausality research design. In measuring these variables researchers used Likert scale, and researchers used questionnairedistribution system. The population in this research are customers of Bank BNI Batu aji batam who came in January toMarch 2020 as many as 363. The sample withdrawal technique used in writing this thesis using the Slovin formula so as toobtain 190 respondents as samples . The t test results, the tcount value of CRM Engine variable is 2,530, greater than thettable 1.653, and the sig value is 0.012 <0.05, it can be concluded that CRM Engine variable has a positive and significanteffect on customer satisfaction variables. The E-channel variable the tcount got 7.972 greater than the ttable value of 1.653and the sig value obtained 0.000 <0.05. It can be concluded that E-channel variable has a positive and significant influenceon the customer satisfaction variable. From the results of the f test, the fcount value of 61.991> ftabel of 2.42 and a sig valueof 0.000 <0.05 so that the results can be concluded simultaneously that the CRM and e-channel variables have a positiveand significant effect on customer satisfaction.